Conversion Of Religion In Muslim Marriage Lives: CONVERSION OF RELIGION IN MUSLIM MARRIAGE LIVES - Agoes Dariyo (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to provide an overview of religious conversion in Muslim marital life. The research used a qualitative approach. The Data collected by interviews, and observation. The number of research subjects was 5 people (1 male and 4 female). The analysis technique is achieved by a triangular approach that involves interviews, observations, and theoretical concepts. The results showed that 2 factors were influencing religious conversion, marriage, and economic factors. Subjects experienced religious conversion through a gradual process, a period of calm, conflict, religious conversion, calm, and a period of expression of religious conversion.